An experimental study of copper electroplating by electrochemical impedance spectroscopy (EIS) at room temperature. (2022) - Parida, Sudeshna; Das, Sanjeev; Mallik, Archana
Abstract: Electrodeposition of metals, which can be used as catalysts for chemical and electrochemical reactions is a very important process from a practical and technical point of view. Copper is frequently used in electrodeposition technology with applications ranging from undercoat for sequentially plated layers to printed circuit board conductors to electroformed products. The present research is copper electrodeposition mechanism from an acidic sulphate solution that has been investigated by EIS in three potentials i.e., −200, −300 and −400 mV and in a frequency range between 10 mHz and 10 kHz with a constant ac potential. EIS spectra consist of two depressed semicircles with a double layer capacitance. All the EIS spectra proposed one equivalent circuit model (ECM) and the EIS parameters were extracted with the help of ECM. The present work contains information about nucleation and the growth stage of electrodeposition of copper on the graphite. The morphology of the copper deposit changes from spherical to powdery as a function of potentials.